Chronic fluoxetine treatment alters cardiovascular functions in unanesthetized rats - Crestani, Carlos Cesar [UNESP]; Tavares, Rodrigo F.; Guimaraes, Franscisco S.; Correa, Fernando M. A.; Joca, Samia R. L.; Resstel, Leonardo B. M. (Elsevier B.V., 2011)
In the present study, we investigated the effects induced by fluoxetine treatment (10 mg/kg) for either 1 or 21 consecutive days on arterial pressure and heart rate basal levels, baroreflex activity, hemodynamic responses to vasoactive agents and cardiovascular responses to acute restraint stress. Mild hypertension was observed after 21 days of treatment, but not after administration for 1 day. Moreover, chronic treatment affected the baroreflex control of heart rate, which was characterized by a reduced reflex tachycardia and an enhanced bradycardiac baroreflex response. The pressor responses to systemic administration of the selective alpha(1)-adrenoceptor agonist phenylephrine, as well as the depressor responses to systemic infusion of the nitric oxide donor sodium nitroprusside, were reduced after chronic fluoxetine treatment. Fluoxetine treatment for 21 days reduced both the pressor and tachycardiac responses evoked by acute restraint stress. In conclusion, the results indicate the development of mild hypertension after chronic fluoxetine treatment. This effect was followed by changes in the baroreflex control of heart rate and altered vascular responsiveness to pressor and depressor agents, which may explain, at least in part, the increase in arterial pressure. Chronic fluoxetine treatment also affected cardiovascular responses to restraint stress, thus indicating that fluoxetine may affect cardiovascular adaptation under conditions of stress. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chronic fluoxetine treatment; Hypertension; Arterial pressure; Heart rate; Baroreflex; Psychological stress